Pathology - Schoelermann, Marc; Neveldine, Mark; Taylor, Brian; Hwang, Christina; Lakeshore Entertainment; Metro-Goldwyn-Mayer Pictures; Camelot Pictures ([California] : Lakeshore Entertainment Group and Metro-Goldwyn-Mayer Studios, 2007)
Med school student Teddy Grey (Milo Ventimiglia) graduates top of his class and joins one of the nation's most prestigious Pathology programs. With talent and determination, Ted is quickly noticed by the program's privileged and elite band of pathology interns who invite him into their crowd. Intrigued by his new friends he begins to uncover secrets he never expected and finds that he has unknowingly become a pawn in their dangerous and secret after-hours game at the morgue of who can commit the perfect undetectable murder. As Ted becomes seduced into their wild extracurricular activities, the danger becomes real and he must stay one step ahead of the game before he is the next victim
Title from container
Executive producer, Ty Van Huisen ; editor, Kye Krauter
Cast: Milo Ventimiglia, Michael Weston, Alyssa Milano, Lauren Lee, Johnny Whitworth, John de Lancie, Mei Melançon, Keir O'Donnell, Dan Callahan, Larry Drake, Alan Blumenfeld, Deborah Pollack, Anne Girard, Jarvis W. George, Don Smith
DVD Format
Dolby Digital
Subtitles in Traiditional Chinese, Simplified Chinese or English
Keywords: Murder -- Drama; Suspense in motion pictures